Maqaṣid Al-Syari’ah: Teori Dan Aplikasi Dalam Istinbaṭh Hukum Islam - Siti Nurjannah (Institut Agama Islam Negeri Metro, 2020)
In the era of digitalization of science and modern information-communication technology, the tradition of legal thought (at-turas) among Islamic legal methodological thinkers (uṣuliyyin) is increasingly developing in the context of extracting law (istinbaṭ al-ahkam). However, the thinking of legal methodology itself is considered by them to have a crisis of methodology in addition to a crisis of paradigm. Meanwhile, various contemporary legal cases (al-waqi'iyyah al-mu'asirah) continue to emerge that demand statutory legal certainty. Even the substance of the methodology of Islamic law (uṣul al-fiqh) is considered by a minority, many of which are no longer relevant to the needs of this modern era. Therefore, as a problem solving to overcome this methodological crisis, the alternative is to rely on maqaṣid asy-syari'ah, both as a doctrine and as a method of ijtihad. Because in its application it is not only based on religious texts (al-Qur'ān and sunnah), but searches and excavations behind the text in an effort to determine and determine legal certainty in every case that occurs. Such application and implementation has been, is being and continues to be developed by contemporary Islamic legal methodological thinkers.